ChemInform Abstract: Three Diketopiperazines from Marine‐Derived Bacteria Inhibit LPS‐Induced Endothelial Inflammatory Responses. Issue 31 (14th July 2016) - Kang, Hyejin; Ku, Sae‐Kwang; Choi, Hyukjae; Bae, Jong‐Sup
Abstract: Three diketopiperazines (Ia), (Ib), and (Ic) are isolated from two strains of marine‐derived bacteria.